Barriers to providing optimal dialysis care for undocumented immigrants: Policy challenges and solutions. Issue 1 (7th January 2020) - Welles, Christine C.; Cervantes, Lilia
Abstract: Access to hemodialysis for undocumented immigrants with end stage renal disease (ESRD) is widely variable across the United States and highly dependent upon state policy. Some states have enacted policies to provide coverage for standard dialysis to undocumented immigrants, while other states do not provide coverage. Patients living in some states which do not provide coverage rely on emergency federal coverage through the Emergency Medical Treatment and Active Labor Act. However, this act requires that patients present with an acute, life‐threatening condition in order to receive dialysis, which is then referred to as "emergency‐only hemodialysis" (EoHD). Because EoHD requires patients to present in life‐threatening condition, patients who rely on EoHD suffer from debilitating physical symptoms and psychosocial distress. Undocumented immigrants who receive EoHD also have staggeringly higher mortality rates than those who receive standard hemodialysis. Moreover, in comparison with standard dialysis, EoHD results in greater health care utilization and higher health care costs. Therefore, EoHD represents a very low value care practice, providing substandard care at a greater cost. Policy change is urgently needed to provide undocumented immigrants with ESRD access to the standard of care; that is, three‐times weekly standard hemodialysis or peritoneal dialysis.